KAJIAN HUBUNGAN RUANG DALAM PADA BANGUNAN GEREJA ST. MARIA FATIMA, SRAGEN, JAWA TENGAH - SRIWINARSIH MARIA KIRANA (Serat Rupa: Journal of Design, 2018)
A building object is real, measurable, and visible, which is built because there are forms, ideas, and expressions. However, from a theory it is revealed that this form is something that is left behind after its mass is no longer attached, but still exists because of its human expression, so that there is a space that still exists even though it is not confined to the physical forming of space. Through this paper it will be shown that the real, measurable, and visible building object are formed not only from the space constrained by the real field or container / scope, but also from a space in between the container which is nonphysical and symbolic. Observation of the object study with Lippsâ€™ space theory approach is the research method that is used. The object of study is the building of St.Maria Fatima church in Sragen, Central Java, a place of expression in worship, the designer wants to convey the message of how the human relationship with God through the relationship of space inside and outside the container. What is expected through this paper is to deepen the insight of designer in designing a building, as not only focus on the physical side. Not just human activity, but also human expression is needed to be expressed.Â Keywords: abstract space; church; symbolic